2019
DOI: 10.1038/s41398-019-0644-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of reward processing in major depressive disorder reveals distinct abnormalities within the reward circuit

Abstract: Many neuroimaging studies have investigated reward processing dysfunction in major depressive disorder. These studies have led to the common idea that major depressive disorder is associated with blunted responses within the reward circuit, particularly in the ventral striatum. Yet, the link between major depressive disorder and reward-related responses in other regions remains inconclusive, thus limiting our understanding of the pathophysiology of major depressive disorder. To address this issue, we performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
116
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 99 publications
1
116
3
1
Order By: Relevance
“…In keeping with this, the integration of experiences could be happening in a different temporal structure. The second reason is that persons with depression are thought to display reward processing aberrations [24][25][26][27] -e.g. in the form of being less sensitive to rewards or learning less from them-that could impact the way in which they integrate across environmental experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with this, the integration of experiences could be happening in a different temporal structure. The second reason is that persons with depression are thought to display reward processing aberrations [24][25][26][27] -e.g. in the form of being less sensitive to rewards or learning less from them-that could impact the way in which they integrate across environmental experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we also examine the generalizability of the models across healthy volunteers and depressed participants, given the wealth of evidence that depression is associated with aberrations in reward processing [24][25][26][27] , which might be also affecting the temporal integration of experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Mice carrying human disease-related genetic mutations exhibit cognitive impairments in the touchscreen-based VD task [19][20][21][22]37]. Previous studies suggested that normal performance in the VD task depends on the intact function of the corticostriatal circuit [20,23], which consists of the PFC, striatum, and thalamus, and is considered to be important for learning behaviors in humans, primates, and rodents [38][39][40]. Therefore, the function of the mPFC was tested using the VD task, which relies on this area and its projection terminals, to assess the impact of the astrocyte pathology and resulting behavioral changes on the computation of cognitive outputs with a high translational validity.…”
Section: Discussionmentioning
confidence: 99%
“…The translational relevance of neural reward processing research is evident from a large and growing literature revealing group differences in regional functional magnetic resonance imaging (fMRI) activation during reward processing across a range of neuropsychiatric conditions, including anxiety, ADHD, depression, addiction, schizophrenia, and autism (Chase et al, 2018;Clements et al, 2018;Forbes et al, 2006;Guyer et al, 2012;Luijten et al, 2017;Ng et al, 2019;Scheres et al, 2007). Building on this work, neural response to reward has been considered a potential biomarker (reflecting the presence of a disorder) or endophenotype (reflecting genetic risk) for these same conditions (Caseras et al, 2013;Dichter, 2012;Grimm et al, 2014;Hasler et al, 2004;Moeller and Paulus, 2018;Pizzagalli, 2014;Rubia, 2018;Sutherland and Stein, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Win > Loss) remains unknown, this prior work may suffer from small sample sizes, and the stability of regions outside of the nucleus accumbens-even of regions known to play key roles in reward processing that have also been implicated in the etiology of neuropsychiatric disorders (e.g. the orbitofrontal cortex (Ng et al, 2019))-has been largely unexplored. As a result, there is limited evidence that these findings generalize.…”
Section: Introductionmentioning
confidence: 99%